The Role of Comic-Based Teaching Materials in German Language Learning - Gusti Noor Amru Hafizhah; Ellychristina D. Hutubess; Liliana Muliastuti (Future Science, 2023)
Teaching materials are one of the external factors that will influence the atmosphere of learning because teaching materials contain curriculum components that students need to master in a subject. Teaching materials have various forms. Nowadays, comics can also act as teaching materials. Comics are one of the reading materials that students like. Comics, which are also known as graphic literature, are a form of visual communication that aims to convey information. Apart from images, there is also written text which is strung together to form an interesting storyline. The role of comics as teaching material is adapted to the learning carried out in schools. One of the lessons that can apply comics as teaching material is German. German is one of the foreign languages studied at the high school level. One way to get students interested in German is to use a variety of teaching materials, one of which is comics. This scientific article uses a qualitative approach in the form of a literature study method. This scientific article examines previous theories and research related to comics to determine the role of comic-based teaching materials in German language learning. The results of the analysis show that the role of comic-based teaching materials can motivate and improve various skills in learning German.